2002
DOI: 10.1046/j.1365-2095.2002.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Flocculated microalgae concentrates as diets for larvae of the tiger prawn Penaeus monodon Fabricius

Abstract: Fresh algal culture is a major bottleneck in the aquaculture industry. Substitutes that are cost-effective and simplify hatchery procedures, such as algae concentrates need to be evaluated. Four species of alga -Chaetoceros muelleri, C. calcitrans, a tropical Skeletonema sp. and Thalassiosira pseudonana -were concentrated by flocculation, stored for 6 weeks at 4°C and then compared with their fresh counterparts as feeds for Penaeus monodon larvae. The algae were fed at either high or low cell densities with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…To harvest microalgal biomass, flocculation is a simple, gentle and cost-effective method and can be used to aggregate microalgal cells to increase the effective "particle" size and hence ease harvesting by centrifugation, filtration or gravity sedimentation. Furthermore, flocculated microalgal concentrates have been directly used as aquaculture feeds (D'Souza et al 2002;Knuckey et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To harvest microalgal biomass, flocculation is a simple, gentle and cost-effective method and can be used to aggregate microalgal cells to increase the effective "particle" size and hence ease harvesting by centrifugation, filtration or gravity sedimentation. Furthermore, flocculated microalgal concentrates have been directly used as aquaculture feeds (D'Souza et al 2002;Knuckey et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has demonstrated that flocculants can interfere in the fatty acid profile of lipids produced by N. oculata, changing the amounts of saturated and unsaturated fatty acids [26]. However, [8,27] obtained good results growing mollusks and crustaceans fed on stored flocculated microalgae biomass.…”
Section: Role Of the Organic Polymermentioning
confidence: 85%
“…Chen (2001Chen ( , 2003 suggested that entrapped cells of S. quadricauda and I. galbana remained alive probably by consuming their reserve of pyrenoids during storage. It was shown that after concentration by floculation the algal cells not only retained their viability and growth-up to 14 days with Chaetoceros calcitrans (McCaustand et al, 1999)-but also their appetence for larvae as above mentioned with the example of C. muelleri or T. pseudonana (D'Souza et al, 2002). Nell and O'Connor (1991) showed also that a combination of P. Pavlova lutheri and C. calcitrans concentrated to a paste and stored up to 14 days at 4 • C produced greater length increases of larvae of Sydney rock oyster than any other fresh or stored, single or combined diet tested.…”
Section: Introductionmentioning
confidence: 93%